Understanding Switched Reluctance Motor Analysis using ANSYS/Maxwell - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
This study focuses on the understanding of N.Fusun Oyman Serteller, switched reluctance motor design and operation theory. It is the one of the most popular electric motor among the modern electric machines. The analysis of the motor is conducted by using the ANSYS/Maxwell software program. Our aim is not only to understand the theory of the motor but also the meaning of the analysis the flux path, the magnetic field lines, the flux density, the vector potential and the effect of all these factors on the discussed motor. Also in this study, the type of material used in rotor design is changed and the effect of this difference is reflected in the figures. © 2020 IEEE.
Keywords: ANSYS/Maxwell; education; magnetic field; switched reluctance motor